Pengaruh Organic Loading Rate (OLR) Tepung Porang terhadap Kinetika Pertumbuhan mikroorganisme Anaerobik - Hotnida Butar Butar; Adrianto Ahmad; Bahruddin Bahruddin (Department of Chemical Engineering, Faculty of Engineering, UNRI, 2026)
Initial substrate concentration (S0) governs the balance between substrate availability, microbial growth, and biomass decay in anaerobic digestion systems. From a bioprocess engineering perspective, inappropriate initial organic load selection leads to misinterpretation of reactor performance when evaluation relies solely on macroscopic indicators. This study applies a Monod-decay kinetic framework to systematically analyze microbial responses to varying initial organic load of konjac flour in batch anaerobic reactors. Initial substrate concentration was modified by adjusting substrate concentration while maintaining identical operational conditions to ensure model consistency. Times-series data of COD, VSS, VFA, alkalinity, and pH were used for parameter estimation through nonlinear regression. Model fitting demonstrated that incorporation of biomass decay significantly improved representation of experimental dynamics, particularly under elevated to initial organic load conditions. Although higher initial organic load increased apparent organic conversion, kinetic parameters revealed a shift toward maintenance-dominated metabolism, reflected by elevated decay coefficients and diminished effective growth rates. Conversely, intermediate initial organic load provided an optimal kinetic window characterized by stable substrate affinity and lower decay intensity. These results confirm that yield formation and COD partitioning are governed by kinetic constrains rather than substrate availability alone. The study highlights the necessity of decay-inclusive models for accurate interpretation and rational design of anaerobic bioprocesses operating under variable organic load.